2022
DOI: 10.1186/s40164-022-00294-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel E-cadherin/SOX9 axis regulates cancer stem cells in multiple myeloma by activating Akt and MAPK pathways

Abstract: Cancer stem cells (CSCs) have been identified in multiple myeloma (MM) and are widely regarded as a key driver of MM initiation and progression. E-cadherin, in addition to its established role as a marker for epithelial-mesenchymal transition, also plays critical roles in controlling the aggressive behaviors of various tumor cells. Here, we show that depletion of E-cadherin in MM cells remarkably inhibited cell proliferation and cell cycle progression, in part through the decreased prosurvival CD138 and Bcl-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Our findings suggest the presence of aberrantly activated Hedgehog and MAPK signaling pathways in CSCs. Studies have confirmed the involvement of the Hedgehog signaling pathway [51,52] and MAPK signaling pathway [53,54] in regulating CSC differentiation and drug resistance. Importantly, by combining Monocle3 pseudotime analysis and prognostic modeling, we have discovered that HSPB1 acts as a regulatory factor in CSCs development, and its high expression indicates a poor prognosis in HCC.…”
Section: Construction and Validation Of Clinical Prediction Modelmentioning
confidence: 86%
“…Our findings suggest the presence of aberrantly activated Hedgehog and MAPK signaling pathways in CSCs. Studies have confirmed the involvement of the Hedgehog signaling pathway [51,52] and MAPK signaling pathway [53,54] in regulating CSC differentiation and drug resistance. Importantly, by combining Monocle3 pseudotime analysis and prognostic modeling, we have discovered that HSPB1 acts as a regulatory factor in CSCs development, and its high expression indicates a poor prognosis in HCC.…”
Section: Construction and Validation Of Clinical Prediction Modelmentioning
confidence: 86%
“…Clonotypic CD138 −/low cells exhibited robust stemness characteristics, drug resistance, and anti-apoptotic potential and a higher ability to sustain in G0 and G1 cell cycle phases [105][106][107].…”
Section: Cancer Surface Marker and Cancer-related Actionmentioning
confidence: 99%
“…In MM CSCs, loss of E-cadherin led to either G0/G1 or G2/M blockade, depending on the cellular milieu, by regulating its crucial cell cycle mediators in each phase, and also limited the side population phenotype. A new regulatory system of MM CSCs through the E-cadherin/SOX9 axis could contribute to the long-term cell survival and outgrowth associated with recurrent/refractory MM [106].…”
Section: Multiple Myeloma (Mm)mentioning
confidence: 99%
“…E-cadherin/SOX9 axis regulated cell growth and self-renewal of cancer stem cells partially through Akt and MAPK signaling in multiple myeloma cells. 20 In addition, the activity of the SOX9-dependent collagen type II alpha 1 enhancer was increased upon the coexpression of a constitutively active MAPK kinase 1 mutant both in primary chondrocytes and C3H10T1/2 cells. 21 Therefore, we hypothesized that SOX9 might promote fibrosis via the MAPK pathways.…”
mentioning
confidence: 94%